Not just a supporting act or a backing vocalist : locating Gertrude Shope in the memory and heritage of the South African liberation struggle : towards a biography - O'Connell, Siona (University of Pretoria, 2025)
Thesis (PhD (Heritage and Museums Studies))--University of Pretoria, 2024.